Reliability and Validity of Questionnaire on Assessing the Aesthetic Perception of Design Motif Applied on Sarawak Pua Kumbu Cloth Using the Art Reception Survey (ARS) - Wan Juliana Emeih Wahed; Saiful Bahari Hj. Mohd Yusoff; Noorhayati Saad (ITB Journal Publisher, LPPM ITB, 2019)
The objective of this study was to assess the reliability of the Art Reception Survey (ARS) in measuring the aesthetic experience of a Pua Kumbu cloth among visitors who visited the textile museums in Kuching Sarawak. Using this instrument with 28 items grouped into 6 factors, the reliability was assessed by measuring its internal consistency using Cronbach's alpha coefficient. Thirty (30) visitors served as respondents in this study, who were from various age groups and different geographic backgrounds. The results from the reliability analysis revealed that the factors had good internal consistency. Cronbach's alpha coefficient ranged from Î± = .672 to .978. The results also indicate that Negative Emotion, Expertise and Positive Attraction produced a low intraclass correlation coefficient. Negative Emotion and the first items from two other factors revealed poor item-scale correlations. This study suggests the removal of the Negative Emotion factor, which was revealed to be irrelevant in measuring the aesthetic experience of the Pua Kumbu cloth, and of items 1 of both Expertise and Positive Attraction, making the remaining 21 items in the instrument reliable to measure the aesthetic experience of the respondents towards the Pua Kumbu cloth.